2019
DOI: 10.1371/journal.pone.0222179
|View full text |Cite
|
Sign up to set email alerts
|

G-protein-coupled receptor 40 agonist GW9508 potentiates glucose-stimulated insulin secretion through activation of protein kinase Cα and ε in INS-1 cells

Abstract: ObjectiveThe mechanism by which G-protein-coupled receptor 40 (GPR40) signaling amplifies glucose-stimulated insulin secretion through activation of protein kinase C (PKC) is unknown. We examined whether a GPR40 agonist, GW9508, could stimulate conventional and novel isoforms of PKC at two glucose concentrations (3 mM and 20 mM) in INS-1D cells.MethodsUsing epifluorescence microscopy, we monitored relative changes in the cytosolic fluorescence intensity of Fura2 as a marker of change in intracellular Ca2+ ([Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…GW9508 is a Gpr40 agonist that has been recently used in studies on atherosclerosis and insulin secretion. 18 , 19 In the present study, we demonstrate the ability of Gpr40 agonism by GW9508 to rescue the protective functions of ESCs exposed to UV-B radiation. These findings demonstrate a novel use of GW9508 as a treatment for UV-B-induced skin damage.…”
Section: Introductionsupporting
confidence: 56%
“…GW9508 is a Gpr40 agonist that has been recently used in studies on atherosclerosis and insulin secretion. 18 , 19 In the present study, we demonstrate the ability of Gpr40 agonism by GW9508 to rescue the protective functions of ESCs exposed to UV-B radiation. These findings demonstrate a novel use of GW9508 as a treatment for UV-B-induced skin damage.…”
Section: Introductionsupporting
confidence: 56%
“…In current researches, GW9508 has been demonstrated to potentiate glucose-stimulated insulin secretion. 18 Also, activation of GPR40 by GW9508 also alleviated epileptic activity in model in vitro. 19 The purpose of this study is to investigate whether the agonism of GPR40 with GW9508 has a beneficial effect against AGE-induced damages in human SW1353 chondrocytes.…”
Section: Introductionmentioning
confidence: 93%
“…PKCs isoenzymes, which belong to the family of serine/threonine kinases, are activated by DAG, which is their main effector [ 221 , 222 , 223 , 224 ]. PKCs are important for a broad range of cellular processes [ 225 ].…”
Section: Revisited Mechanism Of Glucose-stimulated Insulin Secretimentioning
confidence: 99%
“…The results revealed that insulin secretagogues induce transient DAG microdomains, which rapidly recruit both cPKCs (specifically isoforms PKCα, PKCβI and PKCβII) and nPKCs (isoforms PKCδ, PKCε and PKCη), emphasizing the role of DAG in the rapid kinetic control of PKC-mediated phosphorylation. The pharmacological stimulation of GPR40 also activated PKCε at a substimulatory (glucose), while in addition to PKCε, PKCα was also activated at high insulin-stimulating (glucose) [ 224 ]. nPKCs were found to affect cytoskeleton dynamics in a way that eases IGV exocytosis [ 227 ].…”
Section: Revisited Mechanism Of Glucose-stimulated Insulin Secretimentioning
confidence: 99%